Yolkin Ameliorates Effects of the Psychic Stress on the Contact Sensitivity, Cell Proliferation, and Cytokine Production in Mice - Michał Zimecki; Jolanta Artym; Maja Kocięba; Ewa Zaczyńska; Katarzyna Kaleta-Kuratewicz; Jan P. Madej; Piotr Kuropka; Aleksandra Zambrowicz; Łukasz Bobak (Frontiers in Bioscience-Landmark)
Background: Prolonged psychic stress leads to immune suppression, which preferentially affects the cellular immune response. Yolkin is an egg-derived protein with firmly established immunoregulatory activities in rodent models. Objective: The aim of this work was to evaluate the effects of oral administration of yolkin, when mice experience prolonged exposure to immobilization stress, on in vivo and in vitro parameters of contact sensitivity (CS) to oxazolone (OXA). Materials and Methods: BALB/c mice were exposed to 5-day immobilization stress, followed by immunization with OXA. Yolkin was applied in drinking water during stress. Ear thickness and auricle histology, concanavalin A (Con A)- and lipopolysaccharide (LPS)-stimulated production of interferon-gamma (IFN γ) and interleukin 6 (IL-6) in splenocyte cultures, Con A-induced splenocyte proliferation, as well as serum corticosterone levels and thymocyte number were analyzed. Results: We showed that the treatment with stress alone led to a lower thymocyte number and a decreased thickness of the auricle skin. Control mice that were stressed also exhibited an increase in the number and area of pustules in the epidermis. The treatment of stressed mice with yolkin resulted in a partial normalization of several parameters that were lowered in stressed mice, such as auricle thickness, thymus cell content, Con A-induced splenocyte proliferation, production of IFN γ and IL-6. The serum levels of corticosterone were correlated with several histological parameters. Conclusion: Oral administration of yolkin normalizes the antigen-specific and nonspecific parameters of the immune system altered by chronic psychic stress in mice.